EKSPLORASI WARISAN BUDAYA ORANG MELAYU: ETOS KERJA, PANTANG LARANG, PAKAIAN ADAT, BUDAYA DAN BERBAGAI KREASI KERAJINANNYA - Dasmarni; Missy Mairista; Filza Nadila Nasir; An Nisa Alya; Lisa Amelia; Yasnel (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to explore the cultural heritage of the Malay people, encompassing their work ethic, taboos, traditional attire, cultural values, and various forms of traditional crafts. Using a descriptive qualitative approach, this research examines literature sources, cultural observations, and the values still preserved within Malay society today. The Malay work ethic is rooted in religious teachings and social values emphasizing honesty, diligence, and responsibility. Taboos function as a system of norms that maintain harmony between humans, society, and nature. Traditional clothing and crafts—such as songket, weaving, and rattan work—reflect the creativity and distinct cultural identity of the Malay people. The findings reveal that Malay cultural heritage serves not only as a historical legacy but also as a source of moral values and inspiration for shaping the character of younger generations. Therefore, the preservation of Malay culture should be continuously strengthened through education and cultural activities.